Everyday Life in the Spectacular City: Making Home in Dubai By Rana AlMutawa. University of California Press. $29.95. February 2024. ISBN: 0520395069 - Matthew Maclean (Gulf Education and Social Policy Review)
This is a Book Review and does not have an abstract. Please download the PDF or view the article in HTML.